Preservation of minimally processed carrots using the combination of ultrasound and mild heat ascorbic acid - Jiayi Wang; Ning Zhou; Sen Ma; Xiaofei Yang; Jun Xing (Ultrasonics Sonochemistry)
Ultrasound (US) in combination with chemical disinfectants is an efficient and cost-effective hurdle technology for disinfecting minimally processed produce (MPP). However, the demand for non-chemical disinfection methods is increasing. In addition, chemical methods have been ineffective in simultaneously improving the physiological properties and inactivating pathogens in MPP. In this study, a novel and safe method called mild heat ascorbic acid (MHAsA; 1 % AsA at 50 °C) was combined with US to process minimally processed carrots. Physiological properties and microbial inactivation efficacy were analyzed during the storage period (0–5 days). The findings indicated that US-MHAsA induced the highest levels of antioxidant enzymes (superoxide dismutase and catalase) activities and accelerated the glutathione-ascorbate cycle, resulting in lower reactive oxygen species (ROS) and malondialdehyde content compared to US and MHAsA. The efficacy of US-MHAsA in inactivating phenylalanine lyase, the initial enzyme in the lignin synthesis process, was lower than that of US. On the other hand, its ability to inactivate cinnamyl alcohol dehydrogenase, the final enzyme in the process, was better than that of both US and MHAsA. However, there were no significant differences in lignin content among the three groups. The inactivation efficacy against enzymes (polyphenol oxidase and peroxidase) involved in browning was consistent across the three treatments. Analysis of the disinfection efficacy against Escherichia coli O157:H7 and Salmonella Typhimurium revealed that US-MHAsA achieved the lowest cross-contamination incidence (10–12 %) during washing, which was significantly lower than the incidence achieved by US (75–82 %). During the period from day 0 to day 5, two pathogens on carrots in the control group increased from 6.25 to 6.64 log CFU/g, while the lowest counts were observed in the US-MHAsA group, decreasing from 4.44 to 3.74 log CFU/g. However, the counts in the US group increased from 5.22 to 6.32 log CFU/g, and the counts at day 5 were not significantly lower than the control. These findings indicate that US-MHAsA is a novel hurdle technology that effectively reduces the risk of pathogen contamination and enhances the ability of MPP to scavenge ROS.